Case Report: Accidental Ocular Blast Injury To A Farmer’s Eye by Gandhak Potash - Nimisha Nagpal; Pawan Prasher; Inderjit Kaur (Delhi Journal of Ophthalmology)
Ocular exposure to chemical explosions constitute true emergency that can be associated with injuries leading to significant visual morbidities. Herein, we report a case of bilateral eye injury in a 54 year old male farmer due to a chemical explosion while preparing a Gandhak Potash mixture. He presented with multiple charred wounds around his face and embedded particulate matter over the eyelids, conjunctiva and cornea. He underwent superficial debridement of the particulate matter along with conservative management using topical antibiotics, cycloplegics and steroids with good visual outcome. Gandhak potash explosions can be potentially visually devastating. Ophthalmologists, especially those working in agricultural surroundings, should be aware of this mode of injury. Good visual outcome is possible with urgent, appropriate medical intervention.